TINGKAT KELELAHAN TENAGA KESEHATAN TERHADAP PENINGKATAN KEJADIAN INSIDEN KESELAMATAN PASIEN : SCOOPING REVIEW - Ellyda Septiani Pramita; Amel wahyu Meylinda; Atika Putri; Selli Mariska; Aanisah Jamilah (CV. ADIBA AISHA AMIRA, 2026)
Electronic Medical Record (EMR) is an informatics innovation designed to support nurses in improving work efficiency, patient safety, and the quality of care in Emergency Departments (ED). This scoping review analyzes 11 national and international studies to describe how EMR is implemented by emergency nurses. The findings reveal that EMR implementation is influenced by user readiness (attitude, knowledge, and skills), the presence of a Safety Alert System (SAS), completeness of documentation supported by standard operating procedures (SOPs), system interoperability, and reimbursement processes. A well-integrated EMR improves documentation accuracy, streamlines clinical workflow, and reduces the risk of medical errors. However, several challenges persist, including the absence of national SOP standards, lack of SAS in many Indonesian hospitals, and user resistance. Optimizing EMR implementation requires improved technological infrastructure, stronger interoperability, routine training for nurses, and more user-friendly EMR designs